2018
DOI: 10.1002/2017jg003989
|View full text |Cite
|
Sign up to set email alerts
|

Past Summer Temperatures Inferred From Dendrochronological Records of Fitzroya cupressoides on the Eastern Slope of the Northern Patagonian Andes

Abstract: Estimating summer temperature fluctuations over long timescales in southern South America is essential for better understanding the past climate variations in the Southern Hemisphere. Here we developed robust 212 year long basal area increment (BAI) and δ13C chronologies from living temperature‐sensitive Fitzroya cupressoides on the eastern slope of the northern Patagonian Andes (41°S). After removing the increasing trend from the growth records likely due to the CO2 fertilization effect, we tested the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 86 publications
(156 reference statements)
2
12
0
Order By: Relevance
“… P. sylvestris , as a gymnosperm, has higher intrinsic water use efficiency (iWUE, i.e., the ratio of photosynthetic carbon uptake ( A ) to stomatal conductance ( g s ); e.g., Leonardi et al, ) than the two deciduous trees. In accordance with this general rule, in this study, the mean values of iWUE of P. sylvestris , F. sylvatica , and Q. petraea are equal to 99.5, 97.2, and 92.5 μmol CO 2 mol −1 H 2 O, respectively (iWUE calculation performed as in Lavergne et al, ). A larger iWUE can result from either reduced g s or increased A (Scheidegger et al, ).…”
Section: Discussionsupporting
confidence: 77%
“… P. sylvestris , as a gymnosperm, has higher intrinsic water use efficiency (iWUE, i.e., the ratio of photosynthetic carbon uptake ( A ) to stomatal conductance ( g s ); e.g., Leonardi et al, ) than the two deciduous trees. In accordance with this general rule, in this study, the mean values of iWUE of P. sylvestris , F. sylvatica , and Q. petraea are equal to 99.5, 97.2, and 92.5 μmol CO 2 mol −1 H 2 O, respectively (iWUE calculation performed as in Lavergne et al, ). A larger iWUE can result from either reduced g s or increased A (Scheidegger et al, ).…”
Section: Discussionsupporting
confidence: 77%
“…As in related studies, we found that wood δ 13 C is positively correlated with temperature, especially in spring-summer, the season of wood formation, and negatively with summer precipitation and soil moisture ( Table 2) (Ferrio & Voltas, 2005;Gagen et al, 2006;Lavergne et al, 2018;Wu et al, 2015). This shows that dry summers (when high temperature and VPD are pervasive) cause water stress in trees, leading to stomatal downregulation of gas exchange (i.e., low g s and C i ) yielding 13 C-rich wood tissue (McCarroll & Loader, 2004).…”
Section: Previous Conditions As Drivers Of Isotopic Compositionsupporting
confidence: 78%
“…The investigated site is at the Cerro Perito Moreno ski station. It is located ~80 km south from Lavergne et al's (Lavergne et al, 2016; Lavergne et al, 2017; Lavergne et al, 2018) sampling sites. This site was selected because (1) it is far from lakes and thus likely not affected by local moisture sources and (2) it is surrounded by a forest of Nothofagus pumilio trees and located close to the tree line, presenting similar environmental conditions to those of the sites studied in the aforementioned Lavergne et al's studies.…”
Section: Methodsmentioning
confidence: 99%
“…This site was selected because (1) it is far from lakes and thus likely not affected by local moisture sources and (2) it is surrounded by a forest of Nothofagus pumilio trees and located close to the tree line, presenting similar environmental conditions to those of the sites studied in the aforementioned Lavergne et al's studies. Practical reasons were also decisive in choosing the site: The ski station is easily accessible by road and it provides a shelter and reliable power supply, facilities not available on Lavergne et al's (Lavergne et al, 2016; Lavergne et al, 2017; Lavergne et al, 2018) sites. In consequence, we were able to test the isotopic equilibrium hypothesis in a similar environment with the same species as those investigated by Lavergne et al (2016; 2017; 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation